Genetic and Phenotypic Variability in Chinese Patients With Branchio-Oto-Renal or Branchio-Oto Syndrome - Feng, Haifeng; Xu, Hongen; Chen, Bei; Sun, Shuping; Zhai, Rongqun; Zeng, Beiping; Tang, Wenxue; Lu, Wei (Frontiers in Genetics, 2021)
Background: Branchio-oto-renal syndrome (BOR) and branchio-oto syndrome (BOS) are rare autosomal dominant disorders defined by varying combinations of branchial, otic, and renal anomalies. Here, we characterized the clinical features and genetic etiology of BOR/BOS in several Chinese families, then explored the genotypes and phenotypes of BOR/BOS-related genes, as well as the outcomes of auditory rehabilitation in different modalities. Materials and Methods: Probands and all affected family members underwent detailed clinical examinations. Their DNA was subjected to whole-exome sequencing to explore the underlying molecular etiology of BOR/BOS; candidate variants were validated using Sanger sequencing and interpreted in accordance with the American College of Medical Genetics guidelines. In addition, a literature review concerning EYA1 and SIX1 alterations was performed to explore the genotypes and phenotypes of BOR/BOS-related genes. Results: Genetic testing identified the novel deletion (c.1425delC, p.Asp476Thrfs*4; NM_000503.6), a nonsense variant (c.889C>T, p.Arg297*), and two splicing variants in the EYA1 gene (c.1050+1G>T and c.1140+1G>A); it also identified one novel missense variant in the SIX1 gene (c.316G>A, p.Val106Met; NM_005982.4). All cases exhibited a degree of phenotypic variability between or within families. Middle ear surgeries for improving bone-conduction component hearing loss had disappointing outcomes; cochlear implantation (CI) contributed to hearing gains. Conclusion: This is the first report of BOR/BOS caused by the SIX1 variant in China. Our findings increase the numbers of known EYA1 and SIX1 mutations. They also emphasize the usefulness of genetic testing in diagnosis and prevention of BOR/BOS, while demonstrating that CI for auditory rehabilitation is a feasible option in some BOR/BOS patients.